Fungos associados às onicomicoses : prevalência e suscetibilidade a drogas antifúngicas - Maifrede, Simone Bravim (2009)
INTRODUCTION: Onychomycosis is the nail infection caused by a wide spectrum of fungi species, including yeasts, dermatophyte and nondermatophyte mould. Due to the variable susceptibility of the several etiologic agents to the antifungal drugs, the laboratorial diagnosis is being considered an important tool to establish the etiology and to help in the choice of the treatment of onychomycosis. Based on the high percentage of therapeutic flaw in the treatment of onychomycosis, there has been some evident interest in the standardization of the susceptibility tests in vitro of filamentous fungi. OBJECTIVES: To establish the frequency of the onychomycosis in relation to other dermatomycosis; to define the etiology of the onychomycosis by the isolation and identification of the fungi; to compare the pattern of susceptibility among dermatophytes and nondermatophytes mould to drugs such as fluconazole, cetoconazole, itraconazole, miconazole, ciclopirox, terbinafine and griseofulvine. METHODS: The clinical samples were collected by the scratching and/or fragmentation of the nail and the direct microscopic examination was made by the treatment of these samples with potassium hydroxide (KOH) at 20% and Parker ink. The cultures were made in dextrose agar Sabouraud with 0,05 mg.mL-1 of cloranphenicol and agar Mycosel, incubated to room temperature and for a period of up to 15 days. The identification of the filamentous fungi was based on the observation of its macroscopic and microscopic characteristics and the tests of susceptibility in vitro to the antifungal drugs were based on CLSI M38-A reference method. RESULTS: The laboratorial diagnosis of the dermatomycosis was established in 69% of the 1.008 patients with lesions that suggested dermatomycosis sent to the Laboratory of Mycologic Diagnosis from the Dept. of Pathology / UFES, in the period of 03/12/2004 to 08/14/2008. Onychomycosis was diagnosed in 333 patients and the groups of more isolated fungi were: yeasts 55,6%, nondermatophyte mould 27,2% and dermatophytes 17,3%. Dermatophytes were more inhibited in vitro than nondermatophytes ones. Drugs such as fluconazole and griseofulvine inhibited just dermatophytes fungi while terbinafine was the drug which most inhibited both groups of fungi and in low concentrations. The quantification of the inoculum for counting in haemocytometer and in plates of agar Sabouraud revealed that the correctness of the inoculum in espectrofotometer may have established a good correspondence in transmission bands differentiated for the various types of fungi. CONCLUSION: It is necessary to establish the laboratorial diagnosis of the onychomycosis, as these may be caused by several etiologic agents and with different susceptibilities in vitro to several antifungal drugs.